Defensive Protectiontraditional Cultural Expresions (TCE) Masyarakat di Kabupaten Blora - Rinitami Njatrijani (Faculty of Law, Diponegoro University, 2018)
Abstract Traditional Cultural Expressions (TCE) is all the intangible cultural heritage, developed by local communities, collectively or individually in a non-systemic manner and that are inserted in the cultural and spiritual traditions of the communities. The catagories of TK and TCE ... “expressions of folklore in the form of tekstual fonetic or verbal, music, dances, theater, fine art, ritual ceremony”. The legal framework of TCE in Indonesia that can be implemented as contained in the 1945 Constitution of the Republic of Indonesia (Fourth Amendment) Article 32 (1), Article 38 and 39 on Copyright Law Number 28 Year 2014 on Copyright, Law Number 5 Year 2017 on Futherance Culture, Presidential Regulation No.78 Year 2007 on the Convention on Protection of Intangible Cultural Heritage), Permendikbud N0.106 of 2013 on Intangible Cultural Heritage of Indonesia. Further provisions by the state are required to immediately ratify the Traditional Knowledge Bill and EBT into a separate law in Indonesia Defensive protection TCEin Blora community is urgent to be protected as a whole so as not to be abused by others. The process of recording, stipulating, proposing to the Indonesian Conservation Heritage Agency on ICH Unesco's list is the final process of digital documentation in the database of intangible cultural heritage as official data of the state which has a positive impact on the welfare of its supporting community. This research indicates that there are only 16 cultural works for the community in Blora Regency that have been designated as Indonesian Culture Heritage / Intangible Cultural Heritage in accordance with UNESCO Convention Year 2003. While there are still many cultural works that need to be prioritized for immediate recording for next year. (Barong, batik motif etc). Keywords : Defensive Protection, Traditional Cultural Expressions (Tce), Misappropriation, Digital Document. Abstrak TCE/Ekspresi budaya tradisional (EBT) adalah semua warisan budaya tak benda, yang dikembangkan oleh masyarakat lokal, secara kolektif atau individual dengan cara yang tidak sistemik dan disisipkan dalam tradisi budaya dan spiritual masyarakat. Kategori warisan budaya tak benda meliputi tradisi lisan, seni pertunjukkan, praktek-praktek sosial, ritual, perayaan-perayaan, pengetahuan dan praktek mengenai alam dan semesta atau pengetahuan dan ketrampilan untuk menghasilkan kerajinan tradisional. Kerangka hukum EBT di Indonesia yang dapat diimplementasikn sebagaimana terdapat dalam UUD RI Tahun 1945 (Amandemen ke empat) Pasal 32(1), Pasal 38 dan 39 tentang Undang-undang Hak Cipta Nomor 28 Tahun 2014 tentang Hak Cipta, Undang-Undang Nomor 5 Tahun 2017 tentang Undang- Undang Pemajuan Kebudayaan yang lahir dalam rangka melindungi, memanfaatkan dan mengembangkan kebudayaan Indonesia, Perpres RI No.78 Tahun 2007 tentang Konvensi Perlindungan Warisan Budaya Takbenda), Permendikbud N0.106 Tahun 2013 tentang Warisan Budaya Takbenda Indonesia. Diperlukan ketentuan lebih lanjut oleh negara untuk segera mengesahkan RUU Pengetahuan Tradisional dan EBT menjadi Undang-Undang tersendiri di Indonesia.Perlindungan defensif EBT di masyarakat Kabupaten Blora sangat mendesak untuk dilindungi secara keseluruhan agar tidak disalahgunakan oleh pihak lain. Proses pencatatan, penetapan, pengusulanke Badan Warisan Budaya Takbenda Indonesia dalam daftar ICH Unesco merupakanproses akhir dokumentasi secara digital dalam database warisan budaya takbenda sebagai data resmi negara yang memberikan dampak positif bagi kesejahteraan masyarakat pendukungnya.Penelitian ini menunjukkan bahwa baru ada 16 karya budaya bagi masyarakat di Kabupaten Blora yang telah ditetapkan sebagai Warisan Budaya Tak Benda Indonesia/Intangible Cultural Heritagesesuai Konvensi UNESCO Tahun 2003.Sementara masih banyak karya-karya budaya yang perlu diprioritaskan untuk segera dilakukan pencatatan untuk tahun-tahun mendatang.(Barong, motif batik dll). Kata Kunci: Perlindungan Defensif, Ekspresi Budaya Tradisional (EBT), Penyalahgunaan, Dokumen Digital.